Live music in a virtual world: Exuberant flourishing and disability at wheelies nightclub in second life - Kent, M.; Ellis, Katie (2015)
© 2015 Angela Cresswell Jones and Rebecca Jane Bennett. Published by Elsevier Ltd. All rights reserved. This chapter explores the virtual world Second Life and specifically one of its more famous nightclub venues. Wheelies opened in 2006 as a virtual nightclub that catered to both people with disabilities, and those who do not present as such. Its founder and proprietor, Simon Stevens, was the first person in Second Life to have his avatar appear in a wheelchair and helmet, reflecting Stevens' analog identity. Wheelies is famous for its dance floor full of people's avatars both in and out of wheelchairs, dancing and socializing. The club won the Catalyst Revolutionary Award in the United Kingdom in 2008. This chapter initially provides a brief background on the online virtual world Second Life and its history of virtual performance, dancing, and live music. The chapter then focuses, through Wheelies, on identity in this type of digital environment and how it interfaces with music, dance, and disability, and what happens in these spaces where an analog body is absent, but a digital body is a key part of a person's interaction with others and the world.